Arbeidsglede i hjemmesykepleien - Glad, Tone (Nordisk tidsskrift for helseforskning, 2019)
Work enjoyment in home nursing This essay is a reflection on work enjoyment in home care nursing. Nurses describe working days that provide little pleasure. Work enjoyment tends to be the result of nurses’ relationship with colleagues and the people they are in contact with and care for. In interviews, home nurses describe busy days of physical and mental pressure to complete all their tasks. There is little enjoyment and a feeling of inadequacy in their work. They call for space for joy that gives them the possibility to achieve work satisfaction. An attempt is made to describe the factors that promote and constrain work enjoyment in nursing through reflection on home nurses’ experiences and the use of texts from the history of ideas and from nursing.